Theoretical Aspects of Professional Pedagogical Training of Future Tutors to Ensure Continuity of Preschool and Primary Education - Olena Novak (Pedagogical Discourse, 2014)
The process of preparing future tutors to ensure continuity of education in pre-school and primary school in modern conditions is advisable to base on such pedagogical approaches as: personal-oriented, competencе, system. Learner-centered approach includes: getting acquainted with the achievements of modern science teaching and learning excellence of teaching experience; introduction course «Continuity of learning in pre-school and elementary school»; active use in the educational process of future tutors role-playing games, the typical situational problems; benevolent, tolerant and objective attitude to future teachers, their interest in the chosen profession, motivating the importance of continuity in teaching in pre-school and elementary school, encourage self-education, self-realization and self-improvement. Competence approach is implemented by the following measures: focus on the successful practical application of skills to ensure continuity of education in pre-school and primary school in modern terms, not just for their assimilation and accumulation; determining the place of knowledge, skills to ensure continuity of learning in pre-school and primary school among key competencies tutors. The systems approach is careful selection of educational material, based on the analysis of future careers, themes, patterns, compound exercises, situational problems for the workshops.